Age-related decline in the resistance of mice to bacterial infection and in LPS/TLR4 pathway-dependent neutrophil responses - Hornigold, Kirsti; Chu, Julia Y.; Chetwynd, Stephen A.; Machin, Polly A.; Crossland, Laraine; Pantarelli, Chiara; Anderson, Karen E.; Hawkins, Phillip T.; Segonds-Pichon, Anne; Oxley, David; Welch, Heidi C. E. (Frontiers in Immunology, 2022)
Host defense against bacterial and fungal infections diminishes with age. In humans, impaired neutrophil responses are thought to contribute to this decline. However, it remains unclear whether neutrophil responses are also impaired in old mice. Here, we investigated neutrophil function in old mice, focusing on responses primed by lipopolysaccharide (LPS), an endotoxin released by gram-negative bacteria like E. coli, which signals through toll-like receptor (TLR) 4. We show that old mice have a reduced capacity to clear pathogenic E. coli during septic peritonitis. Neutrophil recruitment was elevated during LPS-induced but not aseptic peritonitis. Neutrophils from old mice showed reduced killing of E. coli. Their reactive oxygen species (ROS) production was impaired upon priming with LPS but not with GM-CSF/TNF. Phagocytosis and degranulation were reduced in a partially LPS-dependent manner, whereas impairment of NET release in response to S. aureus was independent of LPS. Unexpectedly, chemotaxis was normal, as were Rac1 and Rac2 GTPase activities. LPS-primed activation of Erk and p38 Mapk was defective. PIP3 production was reduced upon priming with LPS but not with GM-CSF/TNF, whereas PIP2 levels were constitutively low. The expression of 5% of neutrophil proteins was dysregulated in old age. Granule proteins, particularly cathepsins and serpins, as well as TLR-pathway proteins and membrane receptors were upregulated, whereas chromatin and RNA regulators were downregulated. The upregulation of CD180 and downregulation of MyD88 likely contribute to the impaired LPS signaling. In summary, all major neutrophil responses except chemotaxis decline with age in mice, particularly upon LPS priming. This LPS/TLR4 pathway dependence resolves previous controversy regarding effects of age on murine neutrophils and confirms that mice are an appropriate model for the decline in human neutrophil function.